Theorizing crime & deviance a new perspective - Hall, Steve 1955- (SAGE Publications, 2012)
A sophisticated, original book by a rising star. Steve Hall provides a comprehensive critique of existing theories contextualises the philosophies and policy which have informed criminological theory and sets out a new theoretical perfective for criminology and sociology